Threat, emboldenment, or both? The effects of political power on violent hate crimes*. Issue 4 (28th September 2020) - Dugan, Laura; Chenoweth, Erica
Abstract: How do expressions of support or opposition by the U.S. federal government, influence violent hate crimes against specific racial and ethnic minorities? In this article, we test two hypotheses derived from Blalock's (1967) conceptualization of intergroup power contests. The political threat hypothesis predicts that positive government attention toward specific groups would lead to more hateful violence directed against them. The emboldenment hypothesis predicts that negative government attention toward specific groups would also lead to more hateful violence directed against them. Using combined data on U.S. government actions and federal hate crime statistics from 1992 through 2012, vector autoregression models provide support for both hypotheses, depending on the protected group involved. We conclude that during this period, African Americans were more vulnerable to hate crimes motivated by political threat, and Latinx persons were more vulnerable to hate crimes motivated by emboldenment.